Implementation of Project Based Learning (PjBL) Model with Differentiation Approach to Improve Critical Thinking Ability - Anindya Primadayuning Putri; Fida Rachmadiarti; Sunu Kuntjoro (International Journal of Current Educational Research, 2023)
Objective: This study aims to determine the improvement of students' critical thinking skills on solar system material in the project-based learning (PjBL) learning model with a differentiated approach. According to PISA, the results of observations in class VII State JHS 13 Madiun and interviews with several science teachers, Indonesian students' science skills are in a low category. Therefore, an appropriate learning model is needed to facilitate students to improve their critical thinking skills. Methode: This research is classified as a type of quantitative research. The subjects in this study were 30 students of class VII A at State JHS 13 Madiun city and science teachers at JHS 13 Madiun city. Results: The analysis showed that this study's increase in pretest and posttest scores was high, with an N-gain value of 0.72. This study also shows that PjBL learning intensely impacts the critical thinking skills of junior high school students in solar system material with a d-effect size value of 0.79. Novelty: The novelty of this research is to collaborate the PjBL learning model with a differentiated approach. In this study, the syntax of PjBL learning collaborates with a differentiation approach that can facilitate all student characteristics. Project creation in this learning is done based on students' learning style characteristics.